Nano-patterning on multilayer MoS2 via block copolymer lithography for highly sensitive and responsive phototransistors - Heekyeong Park (Nature Portfolio, 2021)
Thin-film phototransistors based on multilayer MoS2 are of great technological importance, but their photoresponsivity may be hindered by an indirect bandgap. Here, nano-patterning of multilayer MoS2 overcomes this limitation by inducing trap states within the bandgap, resulting in a high photoresponsivity of 622.2 A W−1.